Pola Komunikasi Pengasuh Dalam Memahami Pengungkapan Diri Anak Di Panti Asuhan Bina Netra Amal Mulia Kota Bengkulu - Tika, Yori Manis (SENGKUNI Journal (Social Science and Humanities Studies), 2022)
The aim of this research is to determine the communication patterns used by caregivers in understanding children's self-disclosure at the Bina Netra Amal Mulia Orphanage, Bengkulu City. The method used in this research is a qualitative method, this method is used to understand directly based on the facts that appear as they are, how communication patterns occur among caregivers to understand children's self-disclosure at the Bina Netra Amal Mulia Orphanage, Bengkulu City. The results of the research can be concluded that the communication pattern that occurs between caregivers and crew members in understanding children's self-disclosure at the Bina Netra Amal Mulia Orphanage in Bengkulu City is a wheel communication pattern. The wheeled communication pattern used by caregivers towards their foster childrenÂ  in forming independence is of course very important for children with special needs both for themselves now and in the future.Â  The obstacle that occurs in the process of communicating with disabled children at the Bina Netra Amal Mulia orphanage in Bengkulu City is the way the caregiver conveys messages to the children to make them understand what the caregiver means